وسائل الإعلام الجزائرية ودورها في تشكيل اتجاهات طلبة جامعة قسنطينة 3 نحو حملات التلقيح ضد كوفيد 19 - حسني,هلالة; الزاهى,دنيا (University of Eloued جامعة الوادي, 2025)
Abstract: This study examined the role of Algerian media in the public and private sectors in shaping the trends of university students towards coronavirus vaccination campaigns. and conducted on a sample of students of the Faculty of Information, Communication and Audiovisual of the University of Constantine 3, Its basic idea is the ability of Algerian written and audiovisual media to convince elite university students of the need to be vaccinated against COVID-19, as well as to study the cognitive, emotional and behavioural implications of media and communication students' dependence on Algerian media in their direction towards vaccination campaigns.The study found, among other findings, that Algerian media contribute to giving students information about the vaccine and work to shape their attitudes and attitudes towards COVID-19 vaccination campaigns and also seek to guide their behaviors towards adherence to preventive measures, but did not contribute to persuading them personally of the vaccination behavior due to the inconsistent information presented and the lack of confidence in the effectiveness of the vaccine.
دراسة مسحية على عينة من طلبة كلية الإعلام والاتصال والسمعي والبصري
Keywords: وسائل الإعلام الجزائرية; كوفيد 19; الاتجاه; Algerian media; Role; Direction; University students; COVID-19